Role of learning material delivered by short message service in addressing to the gaps in the knowledge of nursing personnel related to newborn care by one of the reviewers in a selected neonatal intensive care unit of tertiary care facility - Joshi, Poonam; Joshi, Meena; Thukra, Anu; Deorari, Ashok K (Indian Journal of Child Health, 2017)
Objectives: The present study was undertaken (i) to evaluate the role of short message service (SMS) in improving the knowledge scores of nurses in the key areas of newborn care (NBC) and (ii) to explore the perception of nurses regarding the delivery of SMS on NBC. Methods: This pre-experimental (one group pre-test post-test) study was conducted on 30 nurses working in a tertiary level neonatal intensive care unit (NICU). The effectiveness of SMS delivery in reducing the gaps in the knowledge of nurses related to NBC was measured in terms of gain in knowledge scores using a structured knowledge questionnaire. The perception of nurses toward the delivery of information on NBC using SMS was also assessed on 5 point likert scale. Results: The knowledge scores of nurses improved significantly after the SMS delivery on NBC (pre and post, 9.6±2.2, 17.13±1.2; p<0.005). The nurses’ overall perception about SMS delivery on NBC was good. Conclusion: SMS delivery on NBC has a potential role in updating and refreshing the knowledge of nurses working in NICU.